2015
DOI: 10.1007/s00253-015-6783-y
|View full text |Cite
|
Sign up to set email alerts
|

Altering small and medium alcohol selectivity in the wax ester synthase

Abstract: The bifunctional wax ester synthase/acyl-coenzyme A:diacylglycerol acyltransferase (WS/DGAT or wax ester synthase) catalyzes the terminal reaction in the bacterial wax ester biosynthetic pathway, utilizing a range of alcohols and fatty acyl-CoAs to synthesize the corresponding wax ester. The wild-type wax ester synthase Maqu_0168 from Marinobacter aquaeolei VT8 exhibits a preference for longer fatty alcohols, while applications with smaller alcohols would yield products with desired biotechnological properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 33 publications
(75 reference statements)
0
53
0
Order By: Relevance
“…MaWSD5-his 6 had a higher WS activity with 18:1 OH compared to 18:0 OH and no WS activity was observed for saturated fatty alcohols of 20 carbons chain length or longer. This observation might be either explained by a different solubility of saturated and desaturated fatty alcohols which can affect the accessibility of the substrate for the enzyme or by spatial limitations of the fatty alcohol binding site (Barney et al, 2013(Barney et al, , 2015Petronikolou and Nair, 2018). The binding site might allow only the binding of fatty alcohols with a certain chain length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MaWSD5-his 6 had a higher WS activity with 18:1 OH compared to 18:0 OH and no WS activity was observed for saturated fatty alcohols of 20 carbons chain length or longer. This observation might be either explained by a different solubility of saturated and desaturated fatty alcohols which can affect the accessibility of the substrate for the enzyme or by spatial limitations of the fatty alcohol binding site (Barney et al, 2013(Barney et al, , 2015Petronikolou and Nair, 2018). The binding site might allow only the binding of fatty alcohols with a certain chain length.…”
Section: Discussionmentioning
confidence: 99%
“…To identify new WSD enzymes in the bacterium M. aquaeolei VT8, a BLAST homology search on the genome of M. aquaeolei VT8 using the amino acid sequence of AbWSD1 was performed. In addition to the four already known and partly characterized WSD MaWSD1, MaWSD2, MaWSD3, and MaWSD4 (Barney et al, 2012(Barney et al, , 2013(Barney et al, , 2015Petronikolou and Nair, 2018;Röttig et al, 2016;Villa et al, 2014), a putative fifth WSD (MaWSD5, Maqu_3411) was identified. While characterizing MaWSD5, the existence of the protein was also mentioned in a book chapter (Knutson et al, 2017).…”
Section: Aquaeolei Vt8 Possesses a Fifth Wsdmentioning
confidence: 95%
“…In addition, mutational analyses of bacterial WSD (Ma1; WP_011783747) from M. aquaeolei VT8 also showed that mutations of 25G, 144 A, 356L, 360A, and 405M sites could alter substrate selectivity to synthesize wax esters of different lengths ( Barney et al, 2013 , 2015 ; Petronikolou et al , 2018 ). However, 259T and 403A sites of SpWSD1 do not have corresponding positions in the Ma1 sequence due to absence of the corresponding structure Ma1 based on the pairwise alignment of the two gene sequences ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant expression analyses of WSD1 in yeast and Escherichia coli revealed predominant wax synthase functions, and showed that it could synthesize different wax ester products, including C34, C40, and C44, using different substrate combinations of primary alcohols and primary acids ( Li et al , 2008 ). The substrate selectivity of WS/DGAT enzymes from Marinobacter aquaeolei can be altered through mutations in specific residues, resulting in the synthesis of different wax ester components ( Barney et al, 2013 , 2015 ; Petronikolou et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…5, 8, 24–25 Currently, the most well studied WS/DGATs are those from Acinetobacter baylyi ADP1 (Ab-WS/DGAT) and Marinobacter aquaeolei VT8 (Ma-WS/DGAT). 12, 14, 2122, 2627 These enzymes have been utilized for the in vivo production of biodiesel and other wax esters by several laboratories, and engineering efforts to alter their substrate specificity have been an area of significant focus. 5, 23, 26, 2833 There is currently no structure available for any member of this enzyme family in the Protein Data Bank (PDB), which limits engineering efforts aimed at altering substrate scope for a given WS/DGAT.…”
Section: Introductionmentioning
confidence: 99%